Alternative technique for biodiesel quality control using an optical fiber long-period grating sensor - Rosane Falate; Karen Nike; Pedro Ramos da Costa Neto; Eduardo Cação Jr.; Marcia Muller; Hypolito José Kalinowski; José Luís Fabris (Química Nova, 2007)
We report the use of an optical fiber sensor to measure the soybean oil concentration in samples obtained from the mixture of pure biodiesel and commercial soybean oil. The operation of the device is based on the long-period grating sensitivity to the surrounding medium refractive index, which leads to measurable modifications in the grating transmission spectrum. The proposed analysis method results in errors in the oil concentration of 0.4% and 2.6% for pure biodiesel and commercial soybean oil, respectively. Techniques of total glycerol, dynamic viscosity, density, and hydrogen nuclear magnetic resonance spectroscopy were also employed to validate the proposed method.